2022
DOI: 10.1155/2022/1643434
|View full text |Cite|
|
Sign up to set email alerts
|

Application Value of the CT Scan 3D Reconstruction Technique in Maxillofacial Fracture Patients

Abstract: Purpose The aim of the study was to explore the application value of computerized tomography (CT) scan 3D reconstruction technology in maxillofacial fracture patients. Methods A total of 80 maxillofacial fracture patients who underwent surgical treatment in Shijiazhuang People's Hospital from January 2019 to January 2020 were enrolled. All of them received 128-slice spiral CT  scans before surgery, and the images were subjected to multiplanar reconstruction (MRP) and volume reconstruction (VR). Results A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Few reports have described living foreign bodies in the human body[ 9 ]. CT constitutes an effective tool for accurate preoperative evaluation of living foreign bodies in clinic[ 3 ]. 3D CT reconstruction clearly displays anatomical structures, lesions and adjacent organs, improving diagnostic accuracy[ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few reports have described living foreign bodies in the human body[ 9 ]. CT constitutes an effective tool for accurate preoperative evaluation of living foreign bodies in clinic[ 3 ]. 3D CT reconstruction clearly displays anatomical structures, lesions and adjacent organs, improving diagnostic accuracy[ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Digestive tract perforation is a common acute abdominal pathology[ 1 , 2 ], often secondary to ulcers, trauma, inflammation, tumors, etc. Computed tomography (CT) constitutes an effective tool for accurate preoperative evaluation of foreign bodies in clinic[ 3 ]. Preoperative three-dimensional (3D) CT reconstruction accurately locates perforation sites and foreign bodies, helps diagnose peritonitis and guides surgical treatment[ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%